WebQuest methodology in Mathematics classes in a Covid-19 pandemic context - Silva, Vítor Marinho (2022)
The teaching of Mathematics in the remote classroom scenario, due to the Covid-19 Pandemic, has involved “arrangements” in teaching activities, from “how to teach” to “how to evaluate” student learning. This work is a qualitative research of exploratory type, which aimed to investigate how the use of the WebQuest methodology can help the mathematics teacher.  The results indicate, on the one hand, that using the WebQuest methodology contributes to the students' learning process. On the other hand, it allows students to communicate with the teacher and develops the ability to learn from investigation and collaboration with other students.